Analysis of parameters influencing the noise emitted by high-voltage power transmission lines - Z. ENGEL; T. WSZOŁEK (Archives of Acoustics)
The paper deals with the phenomena of the noise emitted by high voltage overhead power transmission lines. It contains an analysis of technical parameters of the transmission line: voltage, voltage gradient, configuration as well as technical conditions of the bundle of conductors. Test results for various weather and environmental conditions have been presented, and their influence upon the level and character of the emitted noise spectrum has been discussed. The atmospheric conditions have been pointed out which essentially influence the acoustic climate of the environment. Special attention has been paid to the noise emitted during intensive corona effect, and to the second harmonic of the power transmission line which appears then in the acoustic spectrum.